The influence of auditor ethics, auditor independence and auditor experience with audit fees as moderating variables on auditors in public accounting firms in the Sumatera, Kalimantan, Bali and Eastern of Indonesia Regions - Runtuwene, Cecilia Angelina; Karamoy, Herman; Wokas, Heince R.N. (The Contrarian : Finance, Accounting, and Business Research, 2024)
This research aims to determine the influence of auditor ethics, auditor independency, and auditor experience on audit quality and to find out whether audit fees can moderate the influence of these variables on audit quality. The data used is primary data with the population in this study being auditors who work at public accounting firms in the Sumatera, Kalimantan, Bali & Eastern of Indonesia Regions. In this study, an Area Sample was used which obtained 118 auditors in that area and 60 people responded or 51% of the auditors. The analytical methods used in this research are Multiple Linear Regression and Moderation Regression Analysis using SPSS as a data processing tool. The results show that auditor ethics influence audit quality, while auditor independence and experience do not influence audit quality. Likewise, audit fees cannot moderate the influence of audit ethics, audit independence and auditor experience on audit quality, and also audit fees cannot influence the audit quality.